2020
DOI: 10.51122/neudentj.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Pandemi Sürecinde Diş Hekimliği Uzmanlık Öğrencilerinin Korku ve Anksiyete Düzeylerinin Değerlendirilmesi

Abstract: Amaç: Dünya Sağlık Örgütü tarafından pandemi olarak ilan edilen, koronavirüs hastalığı (COVID-19), ortaya çıkışı ve hızlı yayılımıyla birlikte toplum genelinde özellikle de yüksek risk taşıdıkları için sağlık çalışanlarında, korku ve kaygıya neden olmaktadır. Bu çalışmanın amacı; COVID-19 pandemisinin ülkemizde uzmanlık eğitimi gören diş hekimleri üzerindeki korku ve anksiyete düzeylerine etkisinin incelenmesidir. Gereç ve Yöntemler: Çalışmaya diş hekimliğinde uzmanlık eğitimi almakta olan 164 diş hekimi dahil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Quarantine measures are implemented in many countries against the rapidly spreading COVID-19 epidemic. These measures keep many people isolated and negatively affect human life (Heath et al, 2020;Tekin et al, 2020;Qiu et al, 2020). Studies have shown that the COVID-19 pandemic poses vital risks to people's physical and psychological health (Liu, 2020;Qiu et al, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Quarantine measures are implemented in many countries against the rapidly spreading COVID-19 epidemic. These measures keep many people isolated and negatively affect human life (Heath et al, 2020;Tekin et al, 2020;Qiu et al, 2020). Studies have shown that the COVID-19 pandemic poses vital risks to people's physical and psychological health (Liu, 2020;Qiu et al, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Working in businesses that accommodate people from different parts of the world can cause tourism business employees to experience common psychological disorders such as fear of death, extreme stress, anxiety, depression, and mental distraction. It may cause discomfort Tekin et al, 2020). Findings from studies conducted during the previous Acute…”
Section: Conceptual Frameworkmentioning
confidence: 99%